contestada

y = x2 − 6x + 8
2y + x = 4
The pair of points representing the solution set of this system of equations is

Respuesta :

Answer:

The two intersections are (3/2 , 5/4) and (4,0).

I put two ways to do it. You can pick your favorite of these are try another route if you like.

Step-by-step explanation:

The system is:

[tex]y=x^2-6x+8[/tex]

[tex]2y+x=4[/tex].

I don't know how good at factoring you are but the top equation consists of polynomial expression that has a factor of (x-4).  I see that if I solve 2y+x=4 for 2y I get 2y=-x+4 which is the opposite of (x-4) so -2y=x-4.

So anyways, factoring x^2-6x+8=(x-4)(x-2) because -4+(-2)=-6 while -4(-2)=8.

This is the system I'm looking at right now:

[tex]y=(x-4)(x-2)[/tex]

[tex]-2y=x-4[/tex]

I'm going to put -2y in for (x-4) in the first equation:

[tex]y=-2y(x-2)[/tex]

So one solution will occur when y is 0.

Now assume y is not 0 and divide both sides by y:

[tex]1=-2(x-2)[/tex]

Distribute:

[tex]1=-2x+4[/tex]

Subtract 4 on both sides:

[tex]-3=-2x[/tex]

Divide both sides by -2:

[tex]\frac{-3}{-2}=x[/tex]

[tex]\frac{3}{2}=x[/tex]

[tex]x=\frac{3}{2}[/tex]

Now let's go back to one of the original equations:

2y=-x+4

Divide both sides by 2:

[tex]y=\frac{-x+4}{2}[/tex]

Plug in 3/2 for x:

[tex]y=\frac{\frac{-3}{2}+4}{2}[/tex]

Multiply top and bottom by 2:

[tex]y=\frac{-3+8}{4}[/tex]

[tex]y=\frac{5}{4}[/tex]

So one solution is at (3/2 , 5/4).

The other solution happened at y=0:

2y=-x+4

Plug in 0 for y:

2(0)=-x+4

0=-x+4

Add x on both sides:

x=4

So the other point of intersection is (4,0).

-------------------------------------------------------

The two intersections are (3/2 , 5/4) and (4,0).

Now if you don't like that way:

[tex]y=x^2-6x+8[/tex]

[tex]2y+x=4[/tex]

Replace y in bottom equation with (x^2-6x+8):

[tex]2(x^2-6x+8)+x=4[/tex]

Distribute:

[tex]2x^2-12x+16+x=4[/tex]

Subtract 4 on both sides:

[tex]2x^2-12x+16+x-4=0[/tex]

Combine like terms:

[tex]2x^2-11x+12=0[/tex]

Compare this to [tex]ax^2+bx+c=0[/tex]

[tex]a=2[/tex]

[tex]b=-11[/tex]

[tex]c=12[/tex]

The quadratic formula is

[tex]x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}[/tex]

{Plug in our numbers:

[tex]x=\frac{11 \pm \sqrt{(-11)^2-4(2)(12)}}{2(2)}[/tex]

[tex]x=\frac{11 \pm \sqrt{121-96}}{4}[/tex]

[tex]x=\frac{11 \pm \sqrt{25}}{4}[/tex]

[tex]x=\frac{11 \pm 5}{4}[/tex]

[tex]x=\frac{11+5}{4} \text{ or } \frac{11-5}{4}[/tex]

[tex]x=\frac{16}{4} \text{ or } \frac{6}{4}[/tex]

[tex]x=4 \text{ or } \frac{3}{2}[/tex]

Using 2y+x=4 let's find the correspond y-coordinates.

If x=4:

2y+4=4

Subtract 4 on both sides:

2y=0

Divide both sides by 2:

y=0

So we have (4,0) is a point of intersection.

If x=3/2

2y+(3/2)=4

Subtract (3/2) on both sides:

2y=4-(3/2)

2y=5/2

Divide 2 on both sides:

y=5/4

The other intersection is (3/2 , 5/4).